Classic Hand, Foot, And Mouth Disease in A 4-Year-Old Girl at An Indonesian District Hospital: A Case Report and Focused Narrative Review on Diagnosis and Therapeutic Stewardship - Refa Rahmaddiansyah; Ahmad Lutfi; Aziza AR; Sukarsi Rusti (Majalah Ilmiah METHODA, 2026)
Background: Hand, foot, and mouth disease (HFMD) is a highly contagious enteroviral illness that most commonly affects children younger than five years. Although the classic clinical pattern is readily recognizable, changing viral epidemiology and atypical cutaneous phenotypes may complicate diagnosis and contribute to unnecessary testing or treatment. Case presentation: A 4-year-old previously healthy girl presented to the emergency department of a district hospital in Rokan Hulu, Indonesia, with three days of intermittent low-grade fever, mild upper respiratory symptoms, painful oral ulcers, and a vesiculopapular eruption involving both palms and soles. She was hemodynamically stable, had preserved peripheral perfusion, no respiratory distress, and no neurologic abnormalities. Examination showed three small sublingual ulcers and bilateral palmar and plantar vesicles with superficial erosions and erythema. The diagnosis of classic HFMD was made clinically; herpangina and varicella were considered less likely. She received outpatient treatment and caregiver counselling regarding hydration, nutrition, hygiene, surface disinfection, and warning signs. Conclusion: The case illustrates the diagnostic value of morphology and distribution in classic HFMD and the need for therapeutic stewardship. In uncomplicated disease, supportive care is the standard; microbiologic testing, antibiotics, and unproven antiviral or immunomodulatory therapies are generally unnecessary unless atypical features, severe disease, or bacterial superinfection is present.